ATP‐binding cassette subfamily A, member 4 intronic variants c.4773+3A>G and c.5461‐10T>C cause Stargardt disease due to defective splicing. Issue 7 (20th February 2018) - Jonsson, Frida; Westin, Ida Maria; Österman, Lennart; Sandgren, Ola; Burstedt, Marie; Holmberg, Monica; Golovleva, Irina
Abstract: Purpose: Inherited retinal dystrophies (IRDs) represent a group of progressive conditions affecting the retina. There is a great genetic heterogeneity causing IRDs, and to date, more than 260 genes are associated with IRDs. Stargardt disease, type 1 (STGD1) or macular degeneration with flecks, STGD1 represents a disease with early onset, central visual impairment, frequent appearance of yellowish flecks and mutations in the ATP‐binding cassette subfamily A, member 4 ( ABCA4 ) gene. A large number of intronic sequence variants in ABCA4 have been considered pathogenic although their functional effect was seldom demonstrated. In this study, we aimed to reveal how intronic variants present in patients with Stargardt from the same Swedish family affect splicing. Methods: The splicing of the ABCA4 gene was studied in human embryonic kidney cells, HEK293T, and in human retinal pigment epithelium cells, ARPE‐19, using a minigene system containing variants c.4773+3A>G and c.5461‐10T>C. Results: We showed that both ABCA4 variants, c.4773+3A>G and c.5461‐10T>C, cause aberrant splicing of the ABCA4 minigene resulting in exon skipping. We also demonstrated that splicing of ABCA4 has different outcomes depending on transfected cell type. Conclusion: Two intronic variants c.4773+3A>G and c.5461‐10T>C, both predicted to affect splicing, are indeed disease‐causing mutations due to skipping of exons 33, 34, 39 and 40 of ABCA4 gene. The experimental proof that ABCA4 mutations in STGD patients affect protein function is crucial for their inclusion to future clinical trials; therefore, functional testing of all ABCA4 intronic variants associated with Stargardt disease by minigene technology is desirable.